Interactive methodology for reliability-based structural design and optimization - Stocki, Rafał; Siemaszko, Andrzej; Kleiber, Michał (Computer Assisted Methods in Engineering and Science, 2023)
Recent advances in reliability methods, optimization as well as design sensitivity analysis have resulted in development of computational systems supporting RBDO processes for medium/large structures. For RBDO the efficiency problems are critical and in order to get the optimum design a number of fast approximate methods have been recently proposed. These methods, tested for rather small problems, show acceptable accuracy and speed up computations considerably. However, when applied in the automated way to medium/large scale problems they may cause severe convergence problems or lead to a poor local minimum after expensive computations. Instead of an automated optimization procedure, an interactive approach is proposed. Implemented in the POLSAP-RBO system it allows to combine effective interactive design methods with visual capabilities to efficiently generate optimum design. Benchmark studies of an offshore jacket structure show efficiency of the interactive approach which employs integration, approximation and reduction techniques for maximizing efficiency of RBDO.